Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Toko Yana Mode Meulaboh: Studi Kasus pada Mahasiswi Jurusan Manajemen, Universitas Teuku Umar - Shintia, Febi; Jalil, Ivon (Medan Resource Center, 2025)
This study investigates the extent to which product quality and service quality influence customer satisfaction at Yana Mode Store in Meulaboh. Grounded in the premise that competitive retail performance depends on the ability to deliver superior value, the research addresses the question of whether product quality and service quality significantly affect customer satisfaction, both partially and simultaneously. A quantitative approach was employed, involving 96 Management students selected through accidental sampling. Data were collected using primary survey instruments and analyzed through multiple linear regression with the assistance of Statistical Package for the Social Sciences. The findings reveal that product quality exerts a significant positive effect on customer satisfaction, service quality also demonstrates a significant positive effect, and both variables simultaneously contribute significantly to enhancing customer satisfaction. These results affirm that improving both product attributes and service performance constitutes a strategic pathway to strengthening customer satisfaction in the retail sector.